2006
DOI: 10.3892/or.15.1.207
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of MLL-AF9, MLL and MYC expression is not obligatory for monocyte-macrophage maturation in AML-M5 cell lines carrying t(9;11)(p22;q23)

Abstract: Abstract. The MLL-AF9 oncogene originates from the translocation t(9;11)(p22;q23), which is mainly associated with monocytic acute myeloid leukaemia (AML-M5; FABclassification). In AML-M5 THP-1 cells carrying t(9;11) (p22;q23) and expressing MLL-AF9, we previously showed that MLL-AF9 expression is down-regulated during monocytemacrophage maturation. We have subsequently observed that in a 'rapid-growing' variant of the THP-1 cell line (THP-1-R) MLL-AF9 down-regulation does not occur. MLL fusion proteins (inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Knockdown of MLL-MLLT3 has been previously shown to induce differentiation and cessation of cellular proliferation. 37,38 Our analysis suggests that repression of mir-424-503 by MLL-MLLT3 may help maintain proliferation and prevent cell-cycle arrest and differentiation by mir-424 and mir-503, two putative tumor suppressor microRNAs of the mir-15/16 family. 29,39 Discussion Twenty-three microRNAs were identified that are dynamically expressed during monocytic differentiation of the THP-1 AML cell line.…”
Section: Regulation Of the Mir-424-503 Polycistronmentioning
confidence: 99%
“…Knockdown of MLL-MLLT3 has been previously shown to induce differentiation and cessation of cellular proliferation. 37,38 Our analysis suggests that repression of mir-424-503 by MLL-MLLT3 may help maintain proliferation and prevent cell-cycle arrest and differentiation by mir-424 and mir-503, two putative tumor suppressor microRNAs of the mir-15/16 family. 29,39 Discussion Twenty-three microRNAs were identified that are dynamically expressed during monocytic differentiation of the THP-1 AML cell line.…”
Section: Regulation Of the Mir-424-503 Polycistronmentioning
confidence: 99%
“…Previously, we and others showed that targeted down-regulation of MLL-AF9 in a human leukemia cell line, THP-1, induced strong inhibition of cell proliferation (8,9), but did not affect the terminal differentiation of THP-1 cells (8). Successively, we reported that down-regulation of MLL-AF9 expression is not mandatory for monocyte-macrophage maturation in AML-M5 cells carrying the translocation t(9;11)(p22;q23), hypothesizing that other genes are important for differentiation blockage in leukemogenesis induced by MLL-AF9 (10). In this study, we analyzed the expression patterns of HOXA4, 5,6,7,9,10,11 and MEIS1 by semiquantitative RT-PCR during the monocyte-macrophage differentiation induced by phorbol 12-myristate 13-acetate (PMA) in THP-1 cells.…”
Section: Introductionmentioning
confidence: 77%
“…Successively, we reported that down-regulation of MLL-AF9 expression is not mandatory for monocyte-macrophage maturation in AML-M5 cells carrying the translocation t(9;11)(p22;q23), hypothesizing that other genes are important for differentiation blockage in leukemogenesis induced by MLL-AF9 (10). In this study, we analyzed the expression patterns of HOXA4, 5,6,7,9,10,11 and MEIS1 by semiquantitative RT-PCR during the monocyte-macrophage differentiation induced by phorbol 12-myristate 13-acetate (PMA) in THP-1 cells. The analysis was performed on THP-1 cells which expressed MLL-AF9 even after PMA-induced monocyte-macrophage differentiation, as previously reported (10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations